2019
DOI: 10.31616/asj.2018.0204
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Radiographic Outcomes of Lateral and Posterior Lumbar Interbody Fusion in the Treatment of Degenerative Lumbar Kyphosis

Abstract: Study Design Retrospective case–control study. Purpose To compare surgical invasiveness and radiological outcomes between posterior lumbar interbody fusion (PLIF) and lateral lumbar interbody fusion (LLIF) for degenerative lumbar kyphosis. Overview of Literature LLIF is a minimally invasive interbody fusion technique; however, few reports compared the clinical outcomes of conventional PLIF and LLIF for degenerative lumbar kyphosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
(42 reference statements)
1
16
1
2
Order By: Relevance
“…Lateral-access cage insertion techniques via the retroperitoneal space have been invented to reduce the problems related to TLIF procedures, including lateral lumbar interbody fusion (LLIF) or oblique lateral interbody fusion (OLIF) [ 2 , 4 , 7 , 11 , 12 , 13 , 14 , 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. LLIF is conducted via the intermuscular approach dissecting the psoas muscle; thus, it can cause psoas muscle-related complications, including anterior thigh pain, leg weakness, nerve root injury, and others [ 2 , 4 , 11 , 13 , 14 , 25 , 29 ]. To overcome the problems of LLIF, the OLIF procedure has been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…Lateral-access cage insertion techniques via the retroperitoneal space have been invented to reduce the problems related to TLIF procedures, including lateral lumbar interbody fusion (LLIF) or oblique lateral interbody fusion (OLIF) [ 2 , 4 , 7 , 11 , 12 , 13 , 14 , 15 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. LLIF is conducted via the intermuscular approach dissecting the psoas muscle; thus, it can cause psoas muscle-related complications, including anterior thigh pain, leg weakness, nerve root injury, and others [ 2 , 4 , 11 , 13 , 14 , 25 , 29 ]. To overcome the problems of LLIF, the OLIF procedure has been recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…Dawkar et al [16] in 2010, reported significant improvement of sagittal balance after LLIF procedure and were probably amongst the first authors to do so. Over the last few years, there have been numerous case series on the success of LLIF for spondylolisthesis, adjacent segment disease, scoliosis, stenosis and kyphosis [17][18][19][20].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Many authors have reported LLIF as an excellent management option for adult spinal deformity [17][18][19][20]. Sembrano et al [21] in their study of 147 patients with spinal deformity and sagittal imbalance, compared four approaches ALIF, LLIF, TLIF and posterior spinal fusion, PSF.…”
Section: Llif In Adult Spinal Deformitymentioning
confidence: 99%
See 1 more Smart Citation
“…MIS-LLIF has shown promising outcomes in minimizing the approach-related morbidity. It can minimize soft tissue injury, decrease blood loss, and shorten hospital stay while maintaining the equivalent or improved clinical and radiographic outcomes as compared to the open procedures [ 67 - 69 ]. Sagittal and coronal deformity correction can be performed with large and lordotic cages [ 70 - 74 ].…”
Section: Lateral Lumbar Interbody Fusionmentioning
confidence: 99%